PERFORMANCE EVALUATION OF RECLAIMED ASPLHALT PAVEMENT MATERIALS USIN CRUDE PALM OIL AS A REJUVENATING AGENT - RAFIQ, WAQAS (2023)
Environmental problems and asphalt binder high prices justify the utilization of reclaimed asphalt pavement (RAP) in bituminous mix production. The aged binder has high stiffiness in recycled material and caused different problems such as low fatigue and resistance against cracking and workability issues, that can be answered by utilizing rejuvenating agents.